Observations on blood figure of sheep infected with Dicrocoelium dendriticum - THEODORIDIS (Ι. ΘΕΟΔΩΡΙΔΗΣ), Y.; SOTIRAKI (Σ. ΣΩΤΗΡΑΚΗ), S.; PAPADOPOULOS (Η. ΠΑΠΑΔΟΠΟΥΛΟΣ), E. (Journal of the Hellenic Veterinary Medical Society, 2018)
Total protein, serum albumin, serum iron and haematocrit of 21 mixed breed female sheep were examined in order to clarify the pathogenicity of Dicrocoelium dendriticum in these animals. The animals were placed individually in metabolic cages and divided into three groups depending on the presence of the worm burden, after their slaughtering and liver examination. The first one was composed of six animals with high D. dendriticum burden (4.800-8.180 parasites), the second of seven with a moderate burden (400-2.720 parasites) and the third which was composed of eight animals, was the control and its worm burden ranged between 0 and 37 parasites. In the begining of the experiment, all sheep were treated, with anthelmintic drugs and an insecticide against cestode and nematode parasites and ectoparasites. Additionally, the control group was treated with a drug against D. dendriticum. All sheep were free of Fasciola hepatica and lung nematodes. During the study, three blood samplings were taken for total protein,serum albumin and serum iron and every day for haematocrit. The first blood sampling was taken the same day with the anthelmintic treatment and the other two, three and four weeks later. There were no statistically significant differences when the group mean values were compared either between the different dates of sampling in the same group or between the different groups,with the exception of serum albumin in the highly infected group, which appeared to be improved in the 2nd and 3rd blood examinations. Finalty, according to the not significant changes in the blood figures, in combination with the other radioisotopic measurments, which took place earlier, is concluded, that D. dendriticum, appart from local lesions, does not seem to infuence the animal health in general.